2014
DOI: 10.1155/2014/851692
|View full text |Cite
|
Sign up to set email alerts
|

Subanesthetic Isoflurane Reduces Zymosan-Induced Inflammation in Murine Kupffer Cells by Inhibiting ROS-Activated p38 MAPK/NF-κB Signaling

Abstract: Volatile anesthetic isoflurane (ISO) has immunomodulatory effects. The fungal component zymosan (ZY) induces inflammation through toll-like receptor 2 or dectin-1 signaling. We investigated the molecular actions of subanesthetic (0.7%) ISO against ZY-induced inflammatory activation in murine Kupffer cells (KCs), which are known as the resident macrophages within the liver. We observed that ISO reduced ZY-induced cyclooxygenase 2 upregulation and prostaglandin E2 release, as determined by western blot and radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 47 publications
1
36
0
1
Order By: Relevance
“…Reactive oxygen species, as a signalling factor, is related to some intracellular pathways, many of which are involved in the regulation of cell senescence . The JNK/p38 pathway plays a crucial role in cell aging, and can be activated by ROS . Therefore, we hypothesized that ROS/JNK/p38 signalling activation is the mechanism by which autophagy inhibits MSC aging induced by D‐gal.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species, as a signalling factor, is related to some intracellular pathways, many of which are involved in the regulation of cell senescence . The JNK/p38 pathway plays a crucial role in cell aging, and can be activated by ROS . Therefore, we hypothesized that ROS/JNK/p38 signalling activation is the mechanism by which autophagy inhibits MSC aging induced by D‐gal.…”
Section: Discussionmentioning
confidence: 99%
“…However, ROS, as a kind of signaling factor, are related with some intracellular pathways [31, 61, 62]; many of these signaling pathways are involved in regulation of cell senescence [63]. The Akt/mTOR pathway plays a crucial role in stem cell aging [64, 65], and this signaling could be inhibited by ROS in cancer cells [66, 67].…”
Section: Discussionmentioning
confidence: 99%
“…Prospects for the clinical usage of isoflurane (1.2-2.5%) have been hampered due to its adverse systemic effects [11]; however, our previous studies have shown that subanesthetic isoflurane (0.7%) protects against zymosan-induced lung injury by upregulating antioxidant enzymes and inhibiting inflammatory responses via the reduction of iNOS induction and NO production in neutrophils [7]. Moreover, subanesthetic isoflurane reduces zymosan- induced inflammation in Kupffer cells by inhibiting the NF-κB pathway [13]. In addition, isoflurane preserves ATP-sensitive K + channel activity in the human omental artery during oxidative stress induced by high glucose, which is mediated by NADPH oxidase inhibition [14].…”
Section: Introductionmentioning
confidence: 99%